Testing The Effectiveness Of Burns Healing Of Gel Preparations Jatropagar ( Jatropha Curcas L) Leaf Extract On Male White Rats ( Rattus Norvegicus) - Angelina Tamo Inya; Ivan Junius Mesak (Strada Journal of Pharmacy, 2024)
Indonesia has a variety of traditional medicinal plants for treating burns. One of them is Jatropha leaves which contain active substances such as saponins, tannins, alkaloids and flavonoids which have antibacterial, antioxidant, anticancer and anti-inflammatory properties. The aim of this research was to determine the effectiveness of Jatropha leaf preparations with extract concentrations of 10%, 15%, 20% on healing burns. This research stage includes plant determination, simplicia making, extract making, phytochemical screening testing, physical quality testing of gel preparations and animal testing. The research was experimental by comparing the effectiveness of healing burns in grouped mice and Jatropha leaf extract gel preparations and the most effective formula for healing burn wounds was Jatropha leaf extract gel preparations at concentrations of 10%, 15%, 20%. Statistical test results showed that there was a difference in the duration of healing of burn wounds in male white rats between Jatropha curcas (Jatropha curcas L) leaf gel preparations with concentrations of 10%, 15%, 20%, bioplaceton gel and gel base.